Continuous Color‐Tunable Light‐Emitting Devices Based on Compositionally Graded Monolayer Transition Metal Dichalcogenide Alloys (Adv. Mater. 44/2022). Issue 44 (3rd November 2022) - Pu, Jiang; Ou, Hao; Yamada, Tomoyuki; Wada, Naoki; Naito, Hibiki; Ogura, Hiroto; Endo, Takahiko; Liu, Zheng; Irisawa, Toshifumi; Yanagi, Kazuhiro; Nakanishi, Yusuke; Gao, Yanlin; et al.
Abstract : Light‐Emitting Devices A color‐tunable light‐emitting diode is realized by Jiang Pu, Yasumitsu Miyata, Taishi Takenobu, and co‐workers in article number 2203250 using compositionally graded monolayer transition metal dichalcogenide alloys. By controlling the light‐emitting positions in the alloys, the composition gradient of the bandgap enables continuous and reversible light emission with energies ranging from 2.1 to 1.7 eV. The results provide a new approach for exploring monolayer semiconductor alloy based broadband optoelectronic device applications.